Application of lean manufacturing to increase productivity in the finishing area in an industrial rubber company - La Rosa Castañeda, Daniela Milagros Matilde (2024)
This research work sought to apply the Lean Manufacturing methodology, with the purpose of improving productivity in the finishing area of a rubber company. It has been observed that, in this area, there is a low productivity, due to an absence of a culture of order and cleanliness, and a lack of production control. The application of Lean tools showed a substantial increase in productivity (from 56.47% to 75.86%), this achieving a progress of 34.33% in the finishing area. In addition, in relation to efficiency, the use of average man-hours will be improved from 75.30% to 87.90%, resulting in an improvement of 16.74%. And, according to the efficacy, an increase was found in the quantities produced, on average, which went from a value of 74.99% to 86.3%, this resulting in an increase of 15.07% in the production of 3S 200 mm rings.